Impact of co-creation on innovation capability and firm performance: a structural equation modeling (2017)
Traditional firms used to design products, evaluate marketing messages and control product distribution channels with no costumer interface. With the advancements in interaction technologies, however, users can easily make impacts on firms; the interaction between costumers and firms is now in peak condition in comparison to the past and is no longer controlled by firms. Customers are playing two roles of value creators and consumers simultaneously. We examine the role of co-creation on the influences of innovation capability and firm performance. We develop hypotheses and test them using researcher survey data. The results suggest that implement of co-creation partially mediate the effect of process innovation capability. We discuss the implications of these findings for research and practice on the depict and implement of unique value co-creation model